Health status and pesticide exposure level of terrestrial pesticide applicators in Córdoba, Argentina - Butinof, Mariana (2015)
Fil: Butinof, Mariana. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas. Escuela de Nutrición; Argentina.